Bentuk Campur Kode Ke Luar Dalam Novel Fall In Love With Senior Karya Sonya Nadila : Kajian Sosiolinguistik - Ragil Sri Wahyuningsih; Wawan Hermawan; Nada Vanca Anggrestia; Fatimatus Zahro; Sefira Amelia Rosadha (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Writers often use external code mixing when writing dialogue in youth genre novels. This is because teenagers often use foreign terms when speaking. This research aims to identify and describe the forms of outward mixing in the novel Fall in Love with Senior by Sonya Nadila. The method used in this research is a qualitative descriptive method which focuses more on collecting and analyzing data involving words, narratives and descriptive images. The data collection technique used is the read and record technique. Steps to collect and analyze data include reading the novel "Fall in Love with Senior" carefully, identifying words and phrases that are forms of outward code mixing, and recording the data collected for further analysis. The results of the research show that there are 15 data regarding external code mixing in the form of words and phrases. The purpose of using external code mixing is to express praise, emphasize emotional expressions, provide motivation, and as a form of terms that are often used by teenagers.